2016
DOI: 10.1186/s12864-016-3208-y
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly and analysis of changes in the protein-coding transcriptome of the freshwater shrimp Paratya australiensis (Decapoda: Atyidae) in response to acid sulfate drainage water

Abstract: BackgroundThe atyid shrimp Paratya australiensis occurs in surface freshwater habitats throughout eastern Australia and has been used to study the ecotoxicology of contaminants such as pesticides and metals. The acidification of surface water that can occur after acid sulfate material in soils and sediments is oxidised and subsequently re-wetted is a serious environmental issue in coastal regions and inland riverine floodplains worldwide. Solubilisation of soil-associated minerals can result in high waterborne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…According previous research, GPx is anti-oxidative enzyme that reduces organic and inorganic hydroperoxides to the corresponding alcohols at the expense of reduced glutathione (Borchert et al, 2018). GPx can keep the cellular redox balance and protect against oxidative damage by reducing hydroperoxides at the expense of glutathione (Bain et al, 2016). These results revealed that the upregulation of GST and GPx was involved in stress response and adaptation, and similar upregulation was observed in Sinopotamon henanense (Sun et al 2016).…”
Section: Identification Of Putative Genes For Responding CD Stresssupporting
confidence: 57%
See 1 more Smart Citation
“…According previous research, GPx is anti-oxidative enzyme that reduces organic and inorganic hydroperoxides to the corresponding alcohols at the expense of reduced glutathione (Borchert et al, 2018). GPx can keep the cellular redox balance and protect against oxidative damage by reducing hydroperoxides at the expense of glutathione (Bain et al, 2016). These results revealed that the upregulation of GST and GPx was involved in stress response and adaptation, and similar upregulation was observed in Sinopotamon henanense (Sun et al 2016).…”
Section: Identification Of Putative Genes For Responding CD Stresssupporting
confidence: 57%
“…In recent years, with the development of nextgeneration sequencing, de novo transcriptomic approaches have been increasingly used to investigate physiological process and molecular characteristics of model and non-model organisms (Lou et al, 2017). Additionally, de novo transcriptome provides great breadth and depth of information that can be used to catalog all the genes expressed in the tissue, and facilitates detailed functional research of various proteins (Bain et al, 2016). To get better understanding about the molecular basis responses to Cd stress in E. j. sinensis, we used the comparative transcriptome of the gills to analyze the differentially expressed genes (DEGs) between exposed and unexposed to Cd by using Illumina sequencing platform and quantitative real-time PCR (RT-qPCR).…”
Section: Introductionmentioning
confidence: 99%
“…Although it may appear controversial, there are similitudes between the decapod and the termite neuropeptidomes that would need to be further studied into an evolutionary perspective (Veenstra, 2016). Noteworthy is that for the de novo transcriptome of the freshwater shrimp Paratya australiensis (Decapoda: Atyidae), the termite Z. nevadensis appears as one of the best hits in their species transcriptome comparison (Bain et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Whole transcriptome profiling of the freshwater shrimp, Paratya australiensis has analysed the stress response pathway in response to the short term exposure of acid sulphate drainage water (Bain et al . ). Hepatopancreas transcriptome of mantis shrimp ( Oratosquilla oratoria ) was studied to assess the toxic effect of chromium hexavalent that revealed up regulation of genes associated with protein digestion and absorption to resist the toxic effect (Zhang et al .…”
Section: Current Status Of Transcriptomics In Aquaculturementioning
confidence: 97%